Safety Program for the assembly and disassembly processes of Trópika, habitation module, in the Solar Decathlon 2014 competition - Ortega-Rojas, Adelina (2014)
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2014.